2010
DOI: 10.1002/eqe.983
|View full text |Cite
|
Sign up to set email alerts
|

Self‐centering structural systems with combination of hysteretic and viscous energy dissipations

Abstract: SUMMARY 7This paper presents an innovative set of high-seismic-resistant structural systems termed Advanced FlagShaped (AFS) systems, where self-centering elements are combined in series and/or in parallel with 9 alternative forms of energy dissipation (yielding, friction and viscous damping). AFS systems is developed using the rationale of combining velocity-dependent with displacement-dependent energy dissipation for 11 self-centering systems, particularly to counteract near-fault earthquakes. Non-linear tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(60 citation statements)
references
References 29 publications
0
60
0
Order By: Relevance
“…The use of viscous dampers in parallel to self-centering rocking walls has been proposed as an effective way to control peak story drifts and residual drifts (Kurama 2000). The parallel combination of hysteretic and viscous energy dissipation along with a friction slip mechanism in series connected to the viscous energy dissipation mechanism were found to achieve high levels of seismic performance (Kam et al 2010). The parallel use of viscous dampers and steel SC-MRFs was found capable to simultaneously control inelastic deformations, peak storey drifts, and residual storey drifts (Tzimas et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The use of viscous dampers in parallel to self-centering rocking walls has been proposed as an effective way to control peak story drifts and residual drifts (Kurama 2000). The parallel combination of hysteretic and viscous energy dissipation along with a friction slip mechanism in series connected to the viscous energy dissipation mechanism were found to achieve high levels of seismic performance (Kam et al 2010). The parallel use of viscous dampers and steel SC-MRFs was found capable to simultaneously control inelastic deformations, peak storey drifts, and residual storey drifts (Tzimas et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that ductility demands can significantly decrease by increasing the energy dissipation capacity and the post-yield stiffness ratio of self-centering systems. Recently, Kam et al [28] showed that a parallel combination of self-centering systems of sufficient hysteretic energy dissipation capacity with viscous dampers can achieve superior performance compared to other structural systems, especially when the peak viscous damper force is controlled by implementing a friction slipping element in series with the viscous damper.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the increase in total accelerations of conventional yielding and self-centering systems due to added damping [19,[28][29] should be quantified. A detailed evaluation of the effect of added damping on residual displacements of conventional yielding systems is missing.…”
Section: Introductionmentioning
confidence: 99%
“…the Rangitikei Railway Bridge [1]), while extensive analytical and experimental work has been performed on rocking shear walls in precast structures (e.g. [2], [3], [4]). Furthermore, guidelines addressing this alternative seismic design have been published by several organizations.…”
Section: Introductionmentioning
confidence: 99%